Sustainable low energy cooling : an overview - Parsloe, C. (CIBSE knowledge series ;, 2005)
This publication gives an overview of the main low energy cooling options available to building services engineers. Its aim is to promote awareness of the alternatives available and their suitability for different applications. It is aimed at a target audience of relevant non-experts such as clients, architects and students. However it should also be of use to more experienced engineers as an accessible overview which can be used in discussions with clients and other members of the design team. --